Penerapan Praktek Pembukuan Sederhana Laporan Keuangan Pada Catering Ibu Shofiah - Yolia Krisdiana (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research plans to decide on using simple bookkeeping practices in financial statements at Catering Ibu Shofiah. The motivation behind this research is that, in general, the improvement of the financial department in the simple bookkeeping provided by the business owner must be carried out with careful consideration so that it is clear and can still be understood in the preparation of financial statements even though it does not apply an accounting system. Therefore, business owners who support the creativity of the younger generation will later be able to improve the financial statements in their business which is a value that is reflected in the practice of simple bookkeeping of financial statements at Catering Ibu Shofiah with the good practices so that the work can be done quickly until it is completed